Grease
Patent Information
- Application Number
- JP2023197926
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-22
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2039-08-01
AI Technical Summary
【0015】 本発明によれば、優れた熱伝導性及び耐湿性を有する無機粒子分散樹脂組成物を提供することができる。
Smart Images

Figure 0007632570000007 
Figure 0007632570000001 
Figure 0007632570000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic particle-dispersed resin composition and a method for producing the inorganic particle-dispersed resin composition. [Background technology]
[0002] In recent years, the amount of heat generated by electronic devices has increased with the increase in their performance and miniaturization. However, heat can cause malfunctions of electronic devices, and methods for dissipating heat have been actively researched. For example, a heat sink using a metal plate with high thermal conductivity is used, and heat is dissipated by conducting heat from a heat source to the heat sink. In order to efficiently dissipate heat from the heat source to the heat sink, a heat conductive sheet (heat dissipation sheet) having thermal conductivity is provided between the heat source and the metal plate. Since heat dissipation sheets used in electronic devices and the like are required to have insulating properties in addition to thermal conductivity, for example, a cured product of a heat dissipation resin composition (a heat dissipation resin composition obtained by curing a resin) in which an oxide having insulating properties and thermal conductivity, such as alumina, silica, or zinc oxide, is dispersed in a matrix resin is used as the heat dissipation sheet.
[0003] As a technology for increasing the thermal conductivity of a heat dissipation sheet, a technology has been disclosed that uses nitrides such as aluminum nitride and boron nitride, which have higher thermal conductivity than oxides such as alumina, silica, and zinc oxide (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 016566 [Patent Document 2] JP 2017-210518 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the techniques of Patent Documents 1 and 2, there is a concern that aluminum nitride reacts with moisture in the air or the like to cause hydrolysis, which causes it to degenerate into aluminum hydroxide with low thermal conductivity, resulting in a decrease in thermal conductivity. There is also a concern that performance may deteriorate, such as corrosion caused by ammonia generated by the hydrolysis of aluminum nitride. In other words, the techniques of Patent Documents 1 and 2 have a problem in that they have insufficient moisture resistance. In addition, the techniques of Patent Documents 1 and 2 have limitations on particle size and shape, so other methods are desirable.
[0006] The present invention has been made in order to solve the above-mentioned problems, and an object of the present invention is to provide an inorganic particle-dispersed resin composition having excellent thermal conductivity and moisture resistance, and a method for producing the inorganic particle-dispersed resin composition. [Means for solving the problem]
[0007] The gist and configuration of the present invention are as follows.
[0008] [1] An inorganic particle-dispersed resin composition containing a resin and inorganic particles, The inorganic particles include silica-coated aluminum nitride particles and alumina particles, The silica-coated aluminum nitride particles are an inorganic particle-dispersed resin composition comprising aluminum nitride particles and a silica coating covering the surfaces of the aluminum nitride particles.
[0009] [2] The inorganic particle-dispersed resin composition according to [1], wherein the total content of the inorganic particles is within the range of 60.0 volume % or more and 85.0 volume % or less.
[0010] [3] The inorganic particle-dispersed resin composition according to [1] or [2], wherein the content of the alumina particles in the inorganic particles is 20 volume % or more and 80 volume % or less.
[0011] [4] The inorganic particle-dispersed resin composition according to any one of [1] to [3], wherein the resin is a curable silicone resin.
[0012] [5] The inorganic particle-dispersed resin composition according to [4], wherein the inorganic particle-dispersed resin composition obtained by curing the curable silicone resin has a thermal conductivity of 5.0 W / (m K) or more.
[0013] [6] The inorganic particle-dispersed resin composition according to any one of [1] to [5], wherein the silica-coated aluminum nitride particles have a silicon atom content of 100 ppm by mass or more and 5000 ppm by mass or less.
[0014] [7] A method for producing the inorganic particle-dispersed resin composition according to any one of [1] to [6], comprising the steps of: a particle production step of producing the silica-coated aluminum nitride particles; a mixing step of mixing the inorganic particles including the silica-coated aluminum nitride particles and the alumina particles obtained in the particle production step with the resin, The particle production process includes a first step of covering the surfaces of the aluminum nitride particles with an organosilicon compound having a structure represented by the following formula (1): and a second step of heating the aluminum nitride particles covered with the organosilicon compound at a temperature of 300° C. or higher and 800° C. or lower. [ka] (In formula (1), R is an alkyl group having 4 or less carbon atoms.) Effect of the Invention
[0015] According to the present invention, it is possible to provide an inorganic particle-dispersed resin composition having excellent thermal conductivity and moisture resistance. [Brief description of the drawings]
[0016] [Figure 1] 1 is a flowchart showing an example of a method for producing an inorganic particle-dispersed resin composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Preferred embodiments of the present invention will now be described in detail.
[0018] [Inorganic particle dispersed resin composition] The inorganic particle-dispersed resin composition of the present invention is an inorganic particle-dispersed resin composition containing a resin and inorganic particles. The inorganic particles include silica-coated aluminum nitride particles and alumina particles. The silica-coated aluminum nitride particles include aluminum nitride particles and a silica coating that covers the surfaces of the aluminum nitride particles. The content of the inorganic particles in the inorganic particle-dispersed resin composition is preferably within a range of 60.0 volume % or more and 85.0 volume % or less. In this specification, the term "inorganic particle-dispersed resin composition" may refer to either the inorganic particle-dispersed resin composition itself or a molded product of the inorganic particle-dispersed resin composition (when the resin contained in the inorganic particle-dispersed resin composition is a curable resin, it refers to a cured product of the inorganic particle-dispersed resin composition). Examples of the inorganic particle-dispersed resin composition itself include those in a fluid form, such as adhesives and greases. Examples of molded products of the inorganic particle-dispersed resin composition include cured products such as tapes and sheets.
[0019] <Resin> The resin contained in the inorganic particle-dispersed resin composition of the present invention is not particularly limited, but a thermosetting resin, a thermoplastic resin, a mixture of a thermosetting resin and a thermoplastic resin, etc. are preferable in terms of excellent heat resistance. The resin may be used alone or in a mixture of two or more kinds. In addition, a mixture of a thermosetting resin and its curing agent or curing accelerator may be used.
[0020] Examples of thermosetting resins include silicone resins, epoxy resins, phenolic resins, bismaleimide resins, cyanate resins, urethane resins, (meth)acrylic resins, vinyl ester resins, unsaturated polyester resins, etc. In particular, silicone resins are preferred in applications where heat resistance and flexibility and adhesion are important, and epoxy resins are preferred in that they have good heat resistance, adhesiveness, and electrical properties after curing.
[0021] The silicone resin may be a curable silicone resin such as an addition reaction curable silicone resin, a condensation reaction curable silicone resin, an organic peroxide curable silicone resin, etc. These may be used alone or in combination of two or more types with different viscosities.
[0022] In particular, when the silicone resin is used in an application that emphasizes flexibility and adhesion, it is preferable to use an addition reaction curing liquid silicone resin that does not generate by-products that can cause bubbles, and a silicone resin cured product can be obtained by reacting an organopolysiloxane having an alkenyl group, which is a base polymer, with an organopolysiloxane having a Si-H group, which is a crosslinking agent, at room temperature or by heating in the presence of a curing agent. Specific examples of the organopolysiloxane, which is a base polymer, include those having a vinyl group, an allyl group, a propenyl group, a hexenyl group, etc., as an alkenyl group. In particular, the vinyl group is preferable as the organopolysiloxane. In addition, for example, a platinum metal-based curing catalyst can be used as the curing catalyst, and the amount of addition can be adjusted to achieve the desired hardness of the resin cured product.
[0023] Epoxy resins include bifunctional glycidyl ether type epoxy resins, glycidyl ester type epoxy resins, linear aliphatic epoxy resins, heterocyclic epoxy resins, glycidyl amine type epoxy resins, polyfunctional glycidyl ether type epoxy resins, and the like, which can be used alone or in combination of two or more types.
[0024] Specifically, for example, bifunctional glycidyl ether type epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, hydrogenated bisphenol A type epoxy resins, and biphenyl type epoxy resins. Glycidyl ester type epoxy resins include hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester. Linear aliphatic epoxy resins include epoxidized polybutadiene and epoxidized soybean oil. Heterocyclic epoxy resins include triglycidyl isocyanurate. Glycidylamine type epoxy resins include N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine), 4-(glycidyloxy)-N,N-diglycidylaniline, and 3-(glycidyloxy)-N,N-diglycidylaniline. In addition, examples of polyfunctional glycidyl ether type epoxy resins include phenol novolac type epoxy resins, cresol novolac type epoxy resins, biphenyl aralkyl type epoxy resins, naphthalene aralkyl type epoxy resins, tetrafunctional naphthalene type epoxy resins, and triphenylmethane type epoxy resins.
[0025] When an epoxy resin is used, a curing agent and a curing accelerator may be added.
[0026] Examples of hardeners include alicyclic acid anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and himic anhydride; aliphatic acid anhydrides such as dodecenylsuccinic anhydride; aromatic acid anhydrides such as phthalic anhydride and trimellitic anhydride; bisphenols such as bisphenol A, bisphenol F, and bisphenol S; phenol resins such as phenol-formaldehyde resin, phenol-aralkyl resin, naphthol-aralkyl resin, and phenol-dicyclopentadiene copolymer resin; and organic dihydrazides such as dicyandiamide and adipic dihydrazide.
[0027] Examples of the curing catalyst include amines such as tris(dimethylaminomethyl)phenol, dimethylbenzylamine, 1,8-diazabicyclo(5,4,0)undecene and derivatives thereof, and imidazoles and derivatives thereof such as 2-methylimidazole, 2-ethyl-4-methylimidazole and 2-phenylimidazole.
[0028] The above-mentioned curing agents and curing catalysts can be used alone or in combination of two or more kinds.
[0029] The inorganic particle-dispersed resin composition may contain a resin component having a high molecular weight, i.e., a high molecular weight component, in addition to the above-mentioned resin components. By containing the high molecular weight component, the sheet formability of the inorganic particle-dispersed resin composition, which is capable of retaining the sheet shape when the inorganic particle-dispersed resin composition is formed into a sheet, can be improved.
[0030] Examples of high molecular weight components include phenoxy resins, polyimide resins, polyamide resins, polycarbodiimide resins, cyanate ester resins, (meth)acrylic resins, polyester resins, polyethylene resins, polyethersulfone resins, polyetherimide resins, polyvinyl acetal resins, urethane resins, and acrylic rubbers.
[0031] In particular, from the viewpoint of excellent heat resistance and film formability, phenoxy resin, polyimide resin, (meth)acrylic resin, acrylic rubber, cyanate ester resin, polycarbodiimide resin, etc. are preferred, and phenoxy resin, polyimide resin, (meth)acrylic resin, acrylic rubber are more preferred. These can be used alone or as a mixture or copolymer of two or more kinds.
[0032] The molecular weight of the high molecular weight component is preferably 10,000 to 100,000 in weight average molecular weight, more preferably 20,000 to 50,000 in weight average molecular weight. By adding a weight average molecular weight component in this range, it is possible to maintain a good sheet shape with good handleability. Here, the weight average molecular weight is a polystyrene-equivalent weight average molecular weight using gel permeation chromatography (GPC). Specifically, it can be measured by combining a column (Shodex (registered trademark) LF-804: manufactured by Showa Denko K.K.) and a differential refractive index detector (Shodex (registered trademark) RI-71S: manufactured by Showa Denko K.K.).
[0033] The content of the high molecular weight component is not particularly limited, but in order for the molded product to maintain sheet properties, it is preferably 0.1% by mass to 20% by mass, more preferably 1% by mass to 15% by mass, and even more preferably 2% by mass to 10% by mass, based on the inorganic particle-dispersed resin composition. An addition amount of 0.1% by mass to 20% by mass provides good handling properties and good sheet-formability and film-formability.
[0034] <Inorganic particles> The inorganic particles contained in the inorganic particle-dispersed resin composition of the present invention include at least silica-coated aluminum nitride particles and alumina particles. The inorganic particles may also include other inorganic particles such as boron nitride, silica, zinc oxide, and aluminum hydroxide.
[0035] The silica-coated aluminum nitride particles contained in the inorganic particles include aluminum nitride particles and a silica coating covering the surfaces of the aluminum nitride particles.
[0036] The aluminum nitride particles constituting the silica-coated aluminum nitride particles can be any known product, such as a commercially available product. The aluminum nitride particles can be obtained by any manufacturing method, such as a direct nitridation method in which metal aluminum powder is directly reacted with nitrogen or ammonia, or a reduction nitridation method in which alumina is carbon-reduced while being heated in a nitrogen or ammonia atmosphere to simultaneously carry out a nitridation reaction.
[0037] The aluminum nitride particles may be particles obtained by sintering aggregates of aluminum nitride fine particles into granules. In particular, sintered granules made from high-purity aluminum nitride fine particles having a cumulative volume d50 of about 1 μm can be suitably used as the aluminum nitride particles.
[0038] Here, the high-purity aluminum nitride fine particles refer to particles with a low oxygen content and a small amount of metal impurities. Specifically, for example, high-purity aluminum nitride having an oxygen content of 1 mass% or less and a total content of metal impurities (i.e., metal atoms other than aluminum) of 1000 mass ppm or less is preferable because it can obtain higher thermal conductivity of the aluminum nitride particles contained in the silica-coated aluminum nitride particles. The aluminum nitride particles can be used alone or in combination.
[0039] The oxygen content can be measured by an inorganic analyzer equipped with an infrared detector for oxygen detection. Specifically, the oxygen content can be measured by using an oxygen / nitrogen / hydrogen analyzer (ONH836: manufactured by LECO Japan LLC).
[0040] The total content of metal atoms other than aluminum can be measured using an ICP (Inductively Coupled Plasma) mass spectrometer, etc. Specifically, the total content of metal atoms other than aluminum can be measured using an ICP mass spectrometer (ICPMS-2030: manufactured by Shimadzu Corporation).
[0041] In this specification, the cumulative volume d50 of particles refers to the particle size at which the cumulative volume is 50% for a certain particle size distribution. The cumulative volume d50 is determined from the particle size distribution by the laser diffraction scattering method, and specifically, the cumulative volume d50 can be measured using a laser diffraction / scattering type particle size distribution analyzer (Microtrac MT3300EX2: manufactured by Microtrac BEL Co., Ltd.).
[0042] The shape of the aluminum nitride particles is not particularly limited, and examples thereof include amorphous (crushed), spherical, elliptical, and plate-like (scale-like) shapes. The aluminum nitride particles may be used in the form of a mixture of aluminum nitride particles in which two or more different types of aluminum nitride particles having different shapes and structures are mixed in various ratios. Here, the larger the volume ratio (filling amount) of the aluminum nitride particles constituting the silica-coated aluminum nitride particles to the inorganic particle-dispersed resin composition, the higher the thermal conductivity, which is preferable. In order to increase the thermal conductivity, that is, to increase the filling amount of the aluminum nitride particles, it is preferable that the shape of the aluminum nitride particles is close to a sphere, which reduces the increase in viscosity of the inorganic particle-dispersed resin composition due to the addition of the silica-coated aluminum nitride particles.
[0043] The average aspect ratio of aluminum nitride particles (index of particle shape) is preferably in the range of 0.8 to 1.0, more preferably in the range of 0.85 to 1.0, and even more preferably in the range of 0.9 to 1.0. Here, the average aspect ratio of aluminum nitride particles is the arithmetic mean value of the ratio (D1 / D2) of the minor axis (D1) and major axis (D2) of 100 randomly selected particles measured in electron micrographs. The minor axis (D1) is the minimum length between two parallel lines in the electron micrograph of the aluminum nitride particles, and the major axis (D2) is the maximum length between two parallel lines in the electron micrograph.
[0044] The cumulative volume d50 of the aluminum nitride particles used in the present invention is preferably in the range of 0.2 μm or more and 200 μm or less, more preferably 10 μm or more and 100 μm or less, and further preferably 10 μm or more and 50 μm or less.
[0045] When the cumulative volume d50 of the aluminum nitride particles is within the above-mentioned range, it is possible to form a molded body with a small minimum thickness, and the moisture resistance of the aluminum nitride particles is improved, probably because the silica coating is easy to uniformly cover the surface of the aluminum nitride particles, and the moisture resistance of the inorganic particle-dispersed resin composition is improved. Note that, when silica-coated aluminum nitride particles are produced in the particle production process described below, the effect on thermal conductivity is small even when relatively fine aluminum nitride particles with a cumulative volume d50 of 50 μm or less are used, probably because a thin silica coating layer can be formed.
[0046] The silica coating that constitutes the silica-coated aluminum nitride particles and covers the surfaces of the aluminum nitride particles is, for example, a silica coating produced in a particle production process described below. It is preferable that the silica coating covers the entire surfaces of the aluminum nitride particles. Although aluminum nitride particles have poor moisture resistance, the moisture resistance can be improved by making the surface of the aluminum nitride particles covered with a silica coating. In addition, since aluminum nitride particles have excellent thermal conductivity, the silica-coated aluminum nitride particles also have excellent thermal conductivity. For example, when such silica-coated aluminum nitride particles are put into a hydrochloric acid aqueous solution adjusted to pH 4 and treated at 85°C for 2 hours (i.e., the silica-coated aluminum nitride particles are immersed in a hydrochloric acid aqueous solution adjusted to pH 4 at 85°C for 2 hours), the concentration of ammonia extracted into the hydrochloric acid aqueous solution can be 20mg / L or less, and the particles have extremely excellent moisture resistance. Since the hydrolysis reaction is promoted in an acidic solution more than in air, an accelerated moisture resistance test can be performed by exposing the particles to a hydrochloric acid aqueous solution adjusted to pH 4. Therefore, the moisture resistance of the silica-coated aluminum nitride particles can be evaluated by using a hydrochloric acid aqueous solution with a pH of 4. If the concentration of ammonia is 20mg / L or less, it can be said that the moisture resistance is good. In addition, by using a hydrochloric acid aqueous solution with a pH of 4, chemical resistance can also be compared. The concentration of the extracted ammonia is preferably 10 mg / L or less, and more preferably 6 mg / L or less.
[0047] The silica-coated aluminum nitride particles preferably have a carbon atom content of 1000 mass ppm or less, more preferably 500 mass ppm or less, and even more preferably 300 mass ppm or less. Such silica-coated aluminum nitride particles can better maintain the high thermal conductivity of the aluminum nitride particles, and are also excellent in moisture resistance and insulation. From the viewpoint of moisture resistance, the lower the carbon atom content, the better. Here, in the particle manufacturing process described later, an organic silicone compound having a structure represented by formula (1) is used as a raw material, so the silica-coated aluminum nitride particles often contain carbon atoms, for example, 50 mass ppm or more, or even 60 mass ppm or more. However, as described above, if the carbon atom content is 1000 mass ppm or less, moisture resistance is excellent.
[0048] The carbon atom content can be measured using a carbon-sulfur analyzer that uses a non-dispersive infrared absorption method using a tubular electric furnace. Specifically, it can be measured using a carbon-sulfur analyzer (Carbon Anlyzer EMIA-821: manufactured by Horiba, Ltd.).
[0049] In addition, the silica-coated aluminum nitride particles preferably have an oxygen atom content of 1.60 mass% or less. When the oxygen atom content is 1.60 mass% or less, the thermal conductivity is more excellent. The oxygen atom content of the silica-coated aluminum nitride particles is more preferably 1.5 mass% or less. In addition, the oxygen atom content of the silica-coated aluminum nitride particles is preferably 0.01 mass% or more.
[0050] In addition, the silica-coated aluminum nitride particles have a coverage rate of 70% to 100%, more preferably 95% or less, even more preferably 72% to 90% or less, and particularly preferably 74% to 85% or less, as determined by LEIS analysis. If the coverage rate is 70% to 100%, the moisture resistance is more excellent. If the coverage rate is more than 95%, the thermal conductivity may decrease.
[0051] The coverage (%) of the silica coating (SiO2) that covers the surface of an aluminum nitride particle by LEIS analysis can be calculated using the following formula. (S Al (AlN)-S Al (AlN+SiO2)) / S Al (AlN) x 100 In the above formula, S Al (AlN) is the area of the Al peak of the aluminum nitride particle, and S Al (AlN+SiO2) is the area of the Al peak of silica-coated aluminum nitride particles. The area of the Al peak can be determined by analysis using low energy ion scattering (LEIS), a measurement method that uses an ion source and rare gas as a probe. LEIS is an analysis method that uses rare gas of several keV as incident ions, and is an evaluation method that enables composition analysis of the outermost surface (Reference: The TRC News 201610-04 (October 2016)).
[0052] The silicon atom content of the silica-coated aluminum nitride particles is not particularly limited, but is, for example, 5000 mass ppm or less, preferably 3000 mass ppm or less, more preferably 2800 mass ppm or less, even more preferably 2600 mass ppm or less, and particularly preferably 1500 mass ppm or less.The silicon atom content of the silica-coated aluminum nitride particles is, for example, 100 mass ppm or more, preferably 100 mass ppm or more and 5000 mass ppm or less.The silicon atom content can be measured by ICP method.
[0053] The content of the silica-coated aluminum nitride particles in the inorganic particles is, for example, 20% by volume or more and 80% by volume or less, preferably 30% by volume or more and 70% by volume or less. If it is 20% by volume or more, as described later, by combining with the silica-coated aluminum nitride particles, an inorganic particle-dispersed resin composition having excellent thermal conductivity can be obtained. When the inorganic particles are composed of silica-coated aluminum nitride particles and alumina particles, the content of the silica-coated aluminum nitride particles in the inorganic particles can be calculated by the following formula. Content (volume %) of silica-coated aluminum nitride particles in inorganic particles = Content (volume) of silica-coated aluminum nitride particles / (Content (volume) of silica-coated aluminum nitride particles + Content (volume) of alumina particles) × 100
[0054] The inorganic particles contained in the inorganic particle-dispersed resin composition include alumina particles, which have thermal conductivity and excellent moisture resistance. The alumina particles may be commercially available or other known alumina particles. Known alumina particles such as commercially available products are available in a wide variety of particle sizes and shapes, allowing optimal selection, and are inexpensive. The alumina particles may be obtained by any method, for example, the thermal decomposition method of ammonium alum, the thermal decomposition method of ammonium aluminum carbonate, the underwater spark discharge method of aluminum, the gas phase oxidation method, the hydrolysis method of aluminum alkoxide, or the like.
[0055] The shape of the alumina particles is not particularly limited, and examples thereof include amorphous (fractured), spherical, rounded, and polyhedral shapes.
[0056] The size of the alumina particles is not particularly limited, but it is preferable that the cumulative volume d50 is 0.1 μm or more and 50 μm or less.
[0057] The content of alumina particles in the inorganic particles is, for example, 20% by volume or more and 80% by volume or less, preferably 30% by volume or more and 70% by volume or less. By including 20% by volume or more of alumina particles in the inorganic particles, an inorganic particle-dispersed resin composition having better thermal conductivity can be obtained. When the inorganic particles are composed of silica-coated aluminum nitride particles and alumina particles, the content of alumina particles in the inorganic particles can be calculated by the following formula. Alumina particle content (volume%) = alumina particle content (volume) / (silica-coated aluminum nitride content (volume) + alumina particle content (volume)) × 100
[0058] The inorganic particles may contain other inorganic particles such as boron nitride, silica, zinc oxide, aluminum hydroxide, etc., in addition to the silica-coated aluminum nitride particles and alumina particles. The content of other inorganic particles in the inorganic particles is, for example, 0% by volume or more and 10% by volume or less.
[0059] The inorganic particles may be surface-treated with a silane coupling agent. The silane coupling agent is not particularly limited, but an example thereof is n-decyltrimethoxysilane having an alkyl group as a functional group.
[0060] The inorganic particle-dispersed resin composition of the present invention contains inorganic particles including the silica-coated aluminum nitride particles and alumina particles in a total amount of preferably 60.0% by volume or more and 85.0% by volume or less, more preferably 65.0% by volume or more and 85.0% by volume or less, particularly preferably 70.0% by volume or more and 85.0% by volume or less. The content (volume %) of the inorganic particles is calculated by converting the content (mass %) of each component in the inorganic particle-dispersed resin composition into a volume based on theoretical density and calculating the volume ratio. If the content of the inorganic particles is within the above range, the workability when using the inorganic particle-dispersed resin composition is improved.
[0061] In this way, since the inorganic particles include alumina particles having thermal conductivity and excellent moisture resistance, and silica-coated aluminum nitride particles having excellent thermal conductivity and improved moisture resistance of aluminum nitride by silica coating, an inorganic particle-dispersed resin composition having excellent thermal conductivity and moisture resistance can be formed as shown in the examples described later. The thermal conductivity of the inorganic particle-dispersed resin composition of the present invention can be, for example, 5.0 W / (m·K) or more. In addition, the ammonia concentration measured in [Evaluation of moisture resistance] in the examples described later for the inorganic particle-dispersed resin composition can be, for example, 30 mg / L or less, preferably 26 mg / L or less, and more preferably 10 mg / L or less. In addition, when the resin is a curable resin, the cured product is formed by heating the inorganic particle-dispersed resin composition, for example, at 120° C. for 30 minutes or more. The reason why an inorganic particle-dispersed resin composition having excellent thermal conductivity and moisture resistance can be formed is presumed to be as follows. Both alumina particles and silica-coated aluminum nitride particles contain aluminum atoms, and the two have similar main physical properties such as specific heat, thermal expansion coefficient, dielectric constant, and hardness. Therefore, even if an inorganic particle-dispersed resin composition is formed by mixing two types of inorganic particles, alumina particles and silica-coated aluminum nitride particles, the characteristics of each other are not canceled out. On the other hand, although there is a large difference between the two in moisture resistance, the moisture resistance of the aluminum nitride particles can be improved by using the silica-coated aluminum nitride particles, so that an inorganic particle-dispersed resin composition that utilizes the good thermal conductivity performance of the aluminum nitride particles without impairing the good moisture resistance of the alumina particles is obtained.
[0062] In the inorganic particle-dispersed resin composition, inorganic particles having different particle sizes are used, for example, by using alumina particles having a small particle size (e.g., d50 of 0.1 μm or more and 50 μm or less) and silica-coated aluminum nitride particles having a larger particle size than the alumina particles (e.g., d50 of 10 μm or more and 100 μm or less), the inorganic particle filling amount (volume %) in the inorganic particle-dispersed resin composition can be increased, and the thermal conductivity of the inorganic particle-dispersed resin composition can be increased.
[0063] The higher the thermal conductivity and electrical insulation of the inorganic particle-dispersed resin composition, the more preferable. The thermal conductivity and electrical insulation of the inorganic particle-dispersed resin composition are improved as the content of the silica-coated aluminum nitride particles in the inorganic particle-dispersed resin composition increases.
[0064] The inorganic particle-dispersed resin composition may contain, as necessary, additives other than the inorganic particles and resin, such as a flexibility imparting agent such as silicone, urethane acrylate, butyral resin, acrylic rubber, diene rubber, or a copolymer thereof, a silane coupling agent, a titanium coupling agent, an inorganic ion scavenger, a pigment, a dye, a diluent, a reaction accelerator, or a dispersion stabilizer.
[0065] [Method of manufacturing inorganic particle-dispersed resin composition] The inorganic particle-dispersed resin composition of the present invention can be produced by a method for producing an inorganic particle-dispersed resin composition of the present invention, which comprises a particle production step of producing silica-coated aluminum nitride particles, and a mixing step of mixing inorganic particles including the silica-coated aluminum nitride particles and alumina particles obtained in the particle production step with a resin, wherein the particle production step comprises a first step of covering the surfaces of the aluminum nitride particles with an organosilicone compound having a structure represented by the following formula (1), and a second step of heating the aluminum nitride particles covered with the organosilicone compound at a temperature of 300°C or more and 800°C or less. Such a method for producing an inorganic particle-dispersed resin composition of the present invention will be described in detail with reference to Fig. 1. Fig. 1 is a flow chart showing an example of the method for producing an inorganic particle-dispersed resin composition of the present invention. [ka] (In formula (1), R is an alkyl group having 4 or less carbon atoms.)
[0066] <Particle manufacturing process> The particle production process is a process for producing silica-coated aluminum nitride particles, and includes a first step of covering the surfaces of the aluminum nitride particles with an organosilicon compound containing the structure represented by the above formula (1), and a second step of heating the aluminum nitride particles covered with the organosilicon compound at a temperature of 300°C or higher and 800°C or lower.
[0067] The organosilicon compound used as the raw material of the silica coating constituting the silica-coated aluminum nitride particles can be used without any particular limitation as long as it contains the structure represented by the above formula (1), regardless of whether it is linear, cyclic or branched. The structure represented by formula (1) is a hydrogen siloxane unit in which hydrogen is directly bonded to a silicon atom.
[0068] In the above formula (1), R, which is an alkyl group having 4 or less carbon atoms, is preferably a methyl group, an ethyl group, a propyl group, a t-butyl group, etc., and is particularly preferably a methyl group. In the particle production process, the organosilicon compound used as a raw material is, for example, an oligomer or polymer containing the structure represented by formula (1).
[0069] As the organosilicone compound, for example, at least one of a compound represented by the following formula (2) and a compound represented by the following formula (3) is preferable. [ka] (In formula (2), R1 and R2 each independently represent a hydrogen atom or a methyl group, at least one of R1 and R2 represents a hydrogen atom, and m represents an integer of 0 to 10.) [ka] (In formula (3), n is an integer of 3 to 6.)
[0070] In particular, the cyclic hydrogen siloxane oligomer in which n is 4 in the above formula (3) is excellent in that it can form a uniform coating on the surface of aluminum nitride particles. The weight average molecular weight of the organosilicone compound containing the structure shown in formula (1) is preferably 100 to 2000, more preferably 150 to 1000, and even more preferably 180 to 500. It is presumed that by using an organosilicone compound containing the structure shown in formula (1) with a weight average molecular weight in this range, it is easy to form a thin and uniform coating on the surface of aluminum nitride particles. In addition, in formula (2), m is preferably 1.
[0071] In this specification, the weight average molecular weight is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC), and specifically, the weight average molecular weight can be measured by using a column (Shodex (registered trademark) LF-804, manufactured by Showa Denko K.K.) in combination with a differential refractive index detector (Shodex (registered trademark) RI-71S, manufactured by Showa Denko K.K.).
[0072] The aluminum nitride particles are as described above in the <Inorganic particle-dispersed resin composition>.
[0073] In the first step, the surfaces of the aluminum nitride particles are covered with an organosilicone compound containing the structure represented by the formula (1) above. In the first step, the method is not particularly limited as long as the surface of the aluminum nitride particles can be covered with an organic silicone compound containing the structure represented by formula (1). The method of the first step includes a dry mixing method in which an organic silicone compound is added by spraying while stirring the raw aluminum nitride particles using a general powder mixer, and then dry-mixed to coat the aluminum nitride particles. Examples of the powder mixer include a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd.), a container-rotating V blender, a double cone blender, a ribbon blender having a mixing blade, a screw blender, a closed rotary kiln, and stirring with a stirrer in a closed container using a magnetic coupling. The temperature condition in this case is not particularly limited depending on the boiling point and vapor pressure of the silicone compound containing the structure represented by formula (1), but is preferably 10°C to 200°C, more preferably 20°C to 150°C, and even more preferably 40°C to 100°C.
[0074] As a method for the first step, a gas-phase adsorption method can be used in which the vapor of an organosilicon compound containing the structure represented by formula (1) alone or a mixed gas with an inert gas such as nitrogen gas is attached or deposited on the surface of aluminum nitride particles placed at rest. The temperature conditions in this case are not particularly limited depending on the boiling point and vapor pressure of the silicone compound containing the structure represented by formula (1), but a preferred temperature is 10°C to 200°C, more preferably 20°C to 150°C, and even more preferably 40°C to 100°C. If necessary, the system can be pressurized or depressurized. As an apparatus that can be used in this case, a closed system and an apparatus that can easily replace the gas in the system are preferred, and for example, a glass container, a desiccator, a CVD apparatus, etc. can be used. When the aluminum nitride particles are coated with the organosilicon compound without stirring, the treatment time needs to be longer. However, by intermittently placing the treatment container on a vibrator, it is possible to efficiently treat areas where the powders are in contact with each other and are in the shade, or powders far from the upper gas phase, by moving the position.
[0075] The amount of the organosilicon compound containing the structure represented by formula (1) used in the first step is not particularly limited. In the aluminum nitride particles covered with the organosilicon compound containing the structure represented by formula (1) obtained in the first step, the amount of the coating of the organosilicon compound containing the structure represented by formula (1) is determined based on the specific surface area (m2) of the aluminum nitride particles determined by the BET method. 2 / g) for surface area of 1 m 2 The specific surface area (m2) of the above-mentioned aluminum nitride particles is preferably 0.1 mg or more and 1.0 mg or less, more preferably 0.2 mg or more and 0.8 mg or less, and even more preferably 0.3 mg or more and 0.6 mg or less. The reason for this is that by making the specific surface area 0.1 mg or more, a uniform silica coating with a large amount of coating can be formed in the silica-coated aluminum nitride particles obtained through the second step described later in detail, and by making the specific surface area 1.0 mg or less, a thin silica coating that does not reduce the thermal conductivity of the obtained silica-coated aluminum nitride particles can be formed. Note that the specific surface area (m2) of the above-mentioned aluminum nitride particles, as determined by the BET method, is2 / g) for surface area of 1 m 2 The coating amount of the organosilicon compound containing the structure represented by formula (1) per aluminum nitride particle was calculated by multiplying the mass difference of the aluminum nitride particles before and after coating with the organosilicon compound by the specific surface area (m2) of the aluminum nitride particles determined by the BET method. 2 Surface area (m2) calculated from 2 ) can be calculated by dividing it by
[0076] The specific surface area determined by the BET method can be measured by a nitrogen adsorption BET one-point method using a gas flow method. As an evaluation device, Macsorb HM model-1210 manufactured by Mountech can be used.
[0077] In the second step, the aluminum nitride particles covered with the organosilicon compound obtained in the first step are heated at a temperature of 300° C. or more and 800° C. or less, thereby forming a silica coating on the surface of the aluminum nitride particles. In the second step, a general heating furnace can be used as long as it can heat the aluminum nitride particles coated with the organosilicon compound obtained in the first step at a temperature of 300°C or higher and 800°C or lower, that is, as long as it can maintain the aluminum nitride particles coated with the organosilicon compound obtained in the first step in a temperature range of 300°C or higher and 800°C or lower.
[0078] In the heat treatment of the second step (heating at a temperature of 300°C or more and 800°C or less), the organosilicon compounds containing the structure represented by formula (1) that coat the aluminum nitride particle surface in the early stage of the heat treatment are bonded to each other or to hydroxyl groups on the aluminum nitride particle surface by a dehydrogenation reaction, which is thought to further strengthen the coating. Then, at the end of the heat treatment, the organic groups (alkyl groups having 4 or less carbon atoms) of the organosilicon compounds are decomposed and volatilized. Therefore, the silica coating formed has a low carbon atom content, and the carbon atom content of the silica-coated aluminum nitride particles also becomes low. Therefore, silica-coated aluminum nitride particles having a carbon atom content of 1000 mass ppm or less can be obtained. If the carbon atom content of the silica-coated aluminum nitride particles is 1000 mass ppm or less, the moisture resistance is good, and unevenly distributed carbon particles are unlikely to have an effect of deteriorating properties such as thermal conductivity and insulation.
[0079] Incidentally, silica coating means that the material is coated with a thin film whose main component is silica. However, since there may be multiple inorganic compounds at the interface between the coated silica and the aluminum nitride particle, when analyzing with ToF-SIMS (Time of Flight Secondary Ion Mass Spectrometry, ION-TOF, TOF.SIMS5), recombination of secondary ions and decomposition during ionization may overlap, and segments such as AlSiO4 ions and SiNO ions may be detected as secondary components at the same time. The composite segments analyzed by this ToF-SIMS analysis can also be defined as partial detections when aluminum nitride is silicaized. As a guideline, if the amount of secondary electrons of silica is greater than the other fractions, silica can be considered to be the main component.
[0080] In an experiment to confirm the purity of silica with even greater precision, a silica coating was formed on an aluminum nitride polycrystalline substrate in the same manner, and the surface of the sample was measured using a photoelectron spectroscopy device (XPS: X-ray Photoelectron Spectroscopy, ULVAC-PHI, Quantera II). The kinetic energy of the detected Si-derived photoelectrons was almost identical to the standard silica peak of 103.7 eV, suggesting that most of the silica has a SiO2 structure. Depending on the heating temperature, organic components may remain. As long as the effect of the present invention is not impaired, it is quite possible that organic siloxane components are mixed in.
[0081] The heating temperature (heat treatment temperature) in the second step is 300°C or higher and 800°C or lower. By performing the process within this temperature range, a silica coating having good moisture resistance and thermal conductivity can be formed. Specifically, when the silica coating is heated at 300°C or higher, the moisture resistance is good, possibly because the silica coating becomes dense and difficult to transmit moisture. When the silica coating is heated at 800°C or lower, the thermal conductivity is good. When the heating temperature is 300°C or higher and 800°C or lower, a silica coating is formed uniformly on the surface of the aluminum nitride particles. When the heating temperature is 300°C or higher, the silica coating has excellent insulating properties, and when the heating temperature is 800°C or lower, it is effective in terms of energy cost. The heating temperature is more preferably 400°C or higher, and even more preferably 500°C or higher.
[0082] The heating time is preferably 30 minutes to 6 hours, more preferably 45 minutes to 4 hours, and even more preferably 1 hour to 2 hours. A heat treatment time of 30 minutes or more is preferable in that no decomposition products of the organic group (alkyl group having 4 or less carbon atoms) of the organosilicon compound remain, and a silica coating with a very low carbon atom content is obtained on the surface of the aluminum nitride particles. In addition, a heating time of 6 hours or less is preferable in that silica-coated aluminum nitride particles can be produced efficiently.
[0083] The heat treatment in the second step is preferably performed in an atmosphere containing oxygen gas, for example, in the atmosphere (air).
[0084] After the heat treatment in the second step, the silica-coated aluminum nitride particles may be partially fused together. In that case, by crushing the particles, silica-coated aluminum nitride particles that are not stuck or aggregated can be obtained. The device used for crushing is not particularly limited, but a general crusher such as a roller mill, hammer mill, jet mill, or ball mill can be used.
[0085] Furthermore, after the second step is completed, the first step and the second step may be performed in sequence. That is, the step of performing the first step and the second step in sequence may be repeatedly performed.
[0086] When the surface of the aluminum nitride particles is covered with an organic silicone compound by a gas-phase adsorption method in the first step, the gas-phase adsorption method is capable of forming a uniform and thin silica coating, compared with a coating method using a liquid treatment. Therefore, even if the first step and the second step are performed in sequence multiple times, for example, 2 to 5 times, the aluminum nitride particles can exhibit good thermal conductivity.
[0087] On the other hand, regarding moisture resistance, a positive correlation is observed between the number of steps of sequentially performing the first step and the second step and the moisture resistance. Therefore, the number of steps of sequentially performing the first step and the second step can be freely selected according to the level of moisture resistance required for practical applications.
[0088] The silica-coated aluminum nitride particles obtained by the above particle production process maintain the inherent high thermal conductivity of aluminum nitride particles and also have excellent moisture resistance. In particular, since the silica coating easily uniformly coats the surfaces of the aluminum nitride particles, the moisture resistance of the silica-coated aluminum nitride particles is sufficiently improved.
[0089] <Mixing process> In the mixing step, the inorganic particles including the silica-coated aluminum nitride particles and alumina particles obtained in the particle production step described above are mixed with a resin.
[0090] The resin to be mixed is as described above in <Inorganic particle-dispersed resin composition>.
[0091] The mixing method in the mixing step is not particularly limited as long as it can disperse inorganic particles in resin, and for example, silica-coated aluminum nitride particles, alumina particles, resin, and other additives to be mixed as necessary are supplied all at once or divided into portions to a dispersing / dissolving device, where they are mixed, dissolved, and kneaded. Examples of the dispersing / dissolving device include a mortar mixer, planetary mixer, rotation / revolution mixer, kneader, roll mill, etc., used alone or in appropriate combination, and mixed, dissolved, and kneaded while heating as necessary.
[0092] In addition, when the inorganic particle dispersion resin composition is applied to a substrate film for the purpose of forming a sheet, a solvent can be used to improve workability. The solvent is not particularly limited, but includes ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone, ether solvents such as 1,4-dioxane, tetrahydrofuran, and diglyme, glycol ether solvents such as methyl cellosolve, ethyl cellosolve, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and diethylene glycol methyl ethyl ether, as well as benzyl alcohol, N-methylpyrrolidone, γ-butyrolactone, ethyl acetate, and N,N-dimethylformamide, which can be used alone or in combination. However, the solvent is removed during the manufacturing process so that it is not included in the inorganic particle dispersion resin composition.
[0093] [Cured product] When the resin is a curable type, the above-mentioned inorganic particle-dispersed resin composition is cured with heat or light to obtain a cured product (an inorganic particle-dispersed resin composition obtained by curing a resin). By curing the resin of the above-mentioned inorganic particle-dispersed resin composition, a cured product having excellent thermal conductivity and moisture resistance is obtained. The thermal conductivity of the cured product is, for example, 5.0 W / (m·K) or more. In addition, the cured product has high insulating properties and a volume resistivity of, for example, 1.0×10 12 Ω·cm or more.
[0094] This cured product can be used in various forms such as a sheet, etc. For example, a sheet made of the cured product can be suitably used as a heat dissipation sheet, such as a thermal interface material (TIM) for power devices, power modules, etc.
[0095] When producing a sheet made of a cured product of the inorganic particle-dispersed resin composition, for example, the following method can be used.
[0096] First, the inorganic particle-dispersed resin composition is molded by a compression press or the like in such a manner that both sides are sandwiched between base films, or the inorganic particle-dispersed resin composition is applied onto the base film using an apparatus such as a bar coater, a screen printer, a blade coater, a die coater, or a comma coater.
[0097] Next, the molded or applied inorganic particle-dispersed resin composition is heated to obtain a sheet-like cured product. The heating conditions (curing conditions) are appropriately set depending on the type of resin, and are, for example, a heat treatment at 120° C. for 30 minutes or more.
[0098] The substrate film used in the production of the sheet-shaped cured product is not particularly limited as long as it can withstand the conditions such as heating during the production of the cured product. For example, polyester film, polypropylene film, polyethylene terephthalate film, polyimide film, polyetherimide film, etc. can be mentioned. These films may be multi-layered films combining two or more kinds, and may have a surface treated with a release agent such as a silicone-based release agent. The thickness of the substrate film is preferably 10 μm or more and 100 μm or less.
[0099] The thickness of the sheet made of the cured product is preferably in the range of 20 μm to 500 μm, more preferably 50 μm to 200 μm. When the sheet thickness is within the above range, a sheet with a uniform composition is easily obtained, and good heat dissipation properties are obtained. EXAMPLES
[0100] EXAMPLES Next, the present invention will be specifically described with reference to examples and comparative examples, but the present invention is not limited to these examples in any way. It should be noted that Example 4 should be read as a reference example.
[0101] [Specific surface area (m) of aluminum nitride particles determined by the BET method] 2 / g) for surface area of 1 m 2 Measurement of the amount of organic silicone compound coated per unit area The specific surface area (m2) of aluminum nitride particles determined by the BET method 2 / g) for surface area of 1 m 2 The coating amount (mg) of the organosilicone compound per unit area is calculated by dividing the mass (mg) of the aluminum nitride particles coated with the organosilicone compound, the mass (mg) of the aluminum nitride particles, and the specific surface area (m2) of the aluminum nitride particles determined by the BET method, which is determined by the method described below. 2 / g)] using the following formula (weight change method). The results are shown in the column "Coating amount of organic silicone compound" in the table. [Specific surface area (m) of aluminum nitride particles determined by the BET method] 2 / g) for surface area of 1 m 2The amount of organic silicone compound coated per unit area (mg / m 2 )] = [Aluminum nitride particle mass difference before and after coating with an organosilicon compound (mg)] / [specific surface area of aluminum nitride particles determined by the BET method (m 2 Surface area (m2) calculated from 2 )] (In the formula, [the difference in mass (mg) of the aluminum nitride particles before and after coating with the organosilicon compound] = [the mass (mg) of the aluminum nitride particles coated with the organosilicon compound] - [the mass (mg) of the aluminum nitride particles], [Specific surface area (m) of aluminum nitride particles determined by the BET method] 2 Surface area (m2) calculated from 2 )] = [specific surface area of aluminum nitride particles obtained by the BET method (m 2 / g)] × [mass of aluminum nitride particles (g)].
[0102] [Measurement of carbon atom content in silica-coated aluminum nitride particles] The carbon atom content of the silica-coated aluminum nitride particles was measured by a carbon-sulfur analyzer (Carbon Anlyzer EMIA-821: manufactured by Horiba, Ltd.) using a non-dispersive infrared absorption method with a tubular electric furnace.
[0103] [Measurement of oxygen atom content in silica-coated aluminum nitride particles] The oxygen atom content of the silica-coated aluminum nitride particles was measured using an oxygen / nitrogen / hydrogen analyzer (ONH836: manufactured by LECO Japan LLC) after heating the silica-coated aluminum nitride particles in air at 105°C for 2 hours.
[0104] [Measurement of silicon atom content in silica-coated aluminum nitride particles] The silicon atom content of the silica-coated aluminum nitride particles was measured by the following procedure. (1) Into a 20 cc Teflon (registered trademark) container, 10 cc of a solution prepared by mixing 97% by mass sulfuric acid (super grade, manufactured by Wako Pure Chemical Industries, Ltd.) and ion-exchanged water in a 1:2 (volume ratio) mixture and 0.5 g of a sample (silica-coated aluminum nitride particles) were placed. (2) The Teflon (registered trademark) container was placed into a stainless steel pressure vessel and maintained at 230°C for 15 hours to dissolve the placed sample. (3) The solution mixed in (1) was taken out, and the silicon atom concentration was measured using an ICP (Shimadzu Corporation, ICPS-7510). From the result, the silicon atom content (mass ppm (μg / g)) of the silica-coated aluminum nitride particles was calculated.
[0105] [Measurement of the coverage of silica coating on aluminum nitride particles by LEIS analysis] The coverage rate of the silica coating covering the surface of the aluminum nitride particles was determined by analysis using low energy ion scattering (LEIS) with an ion source and rare gas as a probe. For LEIS, an IONTOF Qtac100 device was used. The incident ions were helium at 3 keV and 6 keV, and neon at 5 keV. The energy spectrum of the backscattered particles was obtained after oxygen cleaning. Based on the values of the areas of the Al peaks of the aluminum nitride particles and the Al peaks of the silica-coated aluminum nitride particles in the energy spectrum, the coverage rate (%) of the silica coating covering the surface of the aluminum nitride particles was calculated using the following formula. (S Al (AlN)-S Al (AlN+SiO2)) / S Al (AlN) x 100 In the above formula, S Al (AlN) is the area of the Al peak of the aluminum nitride particle, and S Al (AlN+SiO2) is the area of the Al peak of the silica-coated aluminum nitride particles.
[0106] [Measurement of specific surface area of aluminum nitride particles using the BET method] The specific surface area of the aluminum nitride particles was measured by the BET method using a Macsorb HM model-1210 manufactured by Mountech Co., Ltd. The adsorption gas used was a mixed gas of 70% by volume of He and 30% by volume of N2. The results are shown in the "BET specific surface area" column in the table.
[0107] [Evaluation of moisture resistance of silica-coated aluminum nitride particles] The moisture resistance of the silica-coated aluminum nitride particles was measured by putting 17 g of a hydrochloric acid aqueous solution adjusted to pH 4 and 3 g of silica-coated aluminum nitride particles into a 50 ml sample tube, sealing it, shaking it in a shaking thermostatic chamber at 60°C or 85°C, 80 rpm, and 2 hours, leaving it to stand, cooling it to room temperature (25°C), and measuring the ammonia concentration in the supernatant at a temperature of 25°C using an ammonia electrode (Ammonia Electrode 5002A: manufactured by Horiba, Ltd.) The results are shown in the "Moisture Resistant Ammonia Concentration" column in Table 1, along with the measurement temperature.
[0108] [Evaluation of thermal conductivity] The thermal conductivity of the resin molded article (cured product) was evaluated as follows. The thermal diffusivity of the resin molded body in the thickness direction was measured at 25°C using a Kyoto Electronics hot disk method thermal property measuring device (TPS2500S). The sample for measuring thermal diffusivity was a resin molded body with a diameter of 3 cm and a thickness of 5 mm. In addition, assuming that simple additivity holds for each component, the theoretical specific heat and theoretical density of the resin molded body were obtained by weighted averaging taking into account the blending amount of each component. The thermal conductivity of the resin molded body was determined by multiplying the thermal diffusivity by the theoretical specific heat and theoretical density. The theoretical specific heat of the resin molded body in each Example and Comparative Example was calculated by setting the theoretical specific heat of the aluminum nitride particles and the silica-coated aluminum nitride particles to 0.73 J / g·K, the theoretical specific heat of the alumina particles to 0.83 J / g·K, and the theoretical specific heat of the resin component (silicone resin) to 1.60 J / g·K. In addition, the theoretical density of the resin molded body in each Example and Comparative Example was calculated by setting the theoretical density of the aluminum nitride particles and the silica-coated aluminum nitride particles to 3.30 g / cm. 3 , the theoretical density of alumina particles is 3.94 g / cm3 , the theoretical density of the resin component is 1.00 g / cm 3 The treatment agent (silane coupling agent) described below is integrated with the resin components and inorganic particles in the cured product, and the amount is small, so it was excluded from the calculation of thermal conductivity.
[0109] [Moisture resistance evaluation] The moisture resistance of the resin molded product was evaluated by placing a resin molded product with a diameter of 3 cm and a thickness of 5 mm in a pressure-resistant container, adding 30 g of ion-exchanged water, sealing it, and then heating it in a hot air oven at 120°C for 24 hours. After heating was completed, it was cooled to room temperature, the pH of the extract was adjusted to 12 or more with an aqueous sodium hydroxide solution, and the ammonia concentration of the supernatant was measured at a temperature condition of 25°C using an ammonia electrode (ammonia electrode 5002A: manufactured by Horiba, Ltd.).
[0110] [Preparation of silica-coated aluminum nitride particles] (Preparation of silica-coated aluminum nitride particles 1) In the first step, the surface coating of aluminum nitride particles was carried out using a vacuum desiccator made of acrylic resin with a thickness of 20 mm, internal dimensions of 260 mm × 260 mm × 100 mm, and a structure divided into two levels, upper and lower, by a partition with through holes. 2 Approximately 30 g of spherical aluminum nitride particles-A (FAN-f80-A1: manufactured by Furukawa Electronics Co., Ltd.) with a molecular weight of 1000 / g were evenly spread on a stainless steel tray and allowed to stand. Next, 10 g of organosilicon compound-A (cyclic methylhydrogensiloxane tetramer: manufactured by Tokyo Chemical Industry Co., Ltd.) where n=4 in formula (3) was placed in a glass petri dish in the lower part of the vacuum desiccator and allowed to stand. After that, the vacuum desiccator was closed and the mixture was heated in an oven at 80°C for 30 hours. The operation was performed while taking safety measures such as releasing hydrogen gas generated by the reaction through an open valve attached to the vacuum desiccator. After the first step was completed, the coating amount of the organosilicon compound containing the structure represented by formula (1) that coated the surface of the aluminum nitride particles was calculated from the specific surface area of the aluminum nitride particles obtained by the BET method, and the coating amount was determined based on the specific surface area per m2 of the surface area.2 The weight was 0.72 mg per particle. After the first step was completed, the sample was taken out of the desiccator and placed in an alumina crucible, and the sample was subjected to a heat treatment in the second step at 650°C for 1.5 hours in air, to obtain silica-coated aluminum nitride particles 1. The respective property values are shown in Table 1.
[0111] (Preparation of silica-coated aluminum nitride particles 2) The aluminum nitride particles-A used as the raw material had a cumulative volume d50 of 30 μm and a specific surface area of 0.11 m as determined by the BET method. 2 Silica-coated aluminum nitride particles 2 were produced in the same manner as for the production of silica-coated aluminum nitride particles 1, except that silica-coated aluminum nitride particles B (FAN-f30-A1: manufactured by Furukawa Electronics Co., Ltd.) having a molecular weight of 1.001 to 1.001 g were used instead. The respective property values are shown in Table 1.
[0112] (Examples 1 to 4, Comparative Examples 1 to 4) [Production of inorganic particle-dispersed resin composition and cured product] First, the types of inorganic particles (silica-coated aluminum nitride particles or aluminum nitride particles, and alumina particles) shown in Table 2 were placed in a container in the composition shown in Table 2, and then charged into a rotary mixer and mixed at 2000 rpm for 30 seconds to produce an inorganic particle mixture. The alumina particles used were rounded alumina-A (AS-10: manufactured by Showa Denko K.K.; crushed alumina with rounded corners) with a cumulative volume d50 of 39 μm, polyhedral alumina-B (AA-5: manufactured by Sumitomo Chemical Co., Ltd.) with a cumulative volume d50 of 6 μm, and polyhedral alumina-C (AA-03: manufactured by Sumitomo Chemical Co., Ltd.) with a cumulative volume d50 of 0.4 μm.
[0113] The obtained inorganic particle mixture was mixed with n-decyltrimethoxysilane as a treatment agent (Z-6210: silane coupling agent, manufactured by Dow Corning Toray Co., Ltd.), and then placed in a planetary mixer. The mixture was stirred twice at 2000 rpm for 30 seconds, and then heat-treated in a hot air oven at 120°C for 1 hour.
[0114] Next, silicone resin was added to the inorganic particle mixture surface-treated with n-decyltrimethoxysilane described above in the formulation shown in Table 2, and the mixture was put into a planetary mixer and stirred three times at 2000 rpm for 30 seconds to obtain an inorganic particle-dispersed resin composition. The silicone resin used was a two-liquid addition-curing silicone rubber (KE-109E: Shin-Etsu Chemical Co., Ltd.) with a liquid A and liquid B ratio of 1:1. The obtained inorganic particle-dispersed resin composition was placed in a cylindrical mold having a diameter of 3 cm and a thickness of 5 mm, and both sides (bottom and top) were sandwiched between copper foil, and both sides were further sandwiched between stainless steel plates. The mixture was then hot-pressed at 120°C for 30 minutes to harden it, producing a resin molded body (cured product).
[0115] The production conditions and properties of the silica-coated aluminum nitride particles are shown in Table 1, and the composition and measurement results are shown in Table 2. The content (volume %) of each particle is calculated based on the theoretical density of aluminum nitride particles and silica-coated aluminum nitride particles of 3.30 g / cm 3 , the theoretical density of alumina particles is 3.94 g / cm 3 The theoretical density of the treatment agent is 0.90 g / cm 3 , the theoretical density of silicone resin is 1.00 g / cm 3 Since the amount of silica coating was extremely small relative to the amount of aluminum nitride particles, the aluminum nitride particles and the silica-coated aluminum nitride particles were calculated as having the same density.
[0116] These results show that the inorganic particle-dispersed resin compositions of Examples 1 to 4, which contain inorganic particles including silica-coated aluminum nitride particles and alumina particles and a resin, can form molded articles having excellent thermal conductivity and moisture resistance, and can form molded articles with improved moisture resistance while maintaining high thermal conductivity, as compared to the compositions of Comparative Examples 1 to 4, which contain a resin and aluminum nitride particles and alumina particles that are not silica-coated.
[0117] [Table 1]
[0118]
Table 2
Claims
[Claim 1] A grease comprising an inorganic particle-dispersed resin composition containing a resin and inorganic particles, the resin is a silicone resin, The inorganic particles include silica-coated aluminum nitride particles and alumina particles, The silica-coated aluminum nitride particles include aluminum nitride particles and a silica coating covering the surfaces of the aluminum nitride particles, The content of the alumina particles in the inorganic particles is 57.0 vol % or more and 80 vol % or less.
Citation Information
Patent Citations
Highly thermally conductive composition
JP2001002830A
Thermally conductive silicone composition and cured product of the same
JP2017210518A
Aluminum nitride-based filler
JP2019034864A
Thermally conductive polysiloxane composition
WO2018016566A1